Chinese regional innovation systems in times of crisis: the case of Guangdong - Henning Kroll; Ulrike Tagscherer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
The dynamic economic development of Guangdong province is one of the most prominent examples of China's catch-up in the course of the past two decades. Once chosen as the nation's first experimental field for the market economy, the province continued to participate above average in national economic growth ever since. Up to today, it maintains a leading position with regard to general industrial performance and average personal income. As China's industry begins to embark on a path of technological up-grading, however, this pre-eminent position begins to be challenged. In the nation's emerging fields of strength, the province's rivals, Beijing and Shanghai, are in a better starting position since they are better endowed with both R&D capacities and qualified human capital. In this context, our paper illustrates the resulting challenges by means of a number of specialized indicators and explains why, despite a continously impres-sive export performance in the high-tech sectors, Guangdong is far from well prepared to maintain its current position. Finally, it briefly describes the policy responses that have been developed, concluding that despite clear evidence of progress some key issues with regard to regional innovation policy appear to remain unaddressed.
urn:nbn:de:0011-n-1102306
Keywords: 330; Innovation; Entwicklungskonvergenz; Innovationspolitik; Regionalpolitik; Guangdong; Standortwettbewerb; Beijing; Schanghai